Regulasi Emosi dalam Persfektif Islam - Harmalis Harmalis (Departement of Mathematics Education, 2022)
Emotions are one of the psychological aspects that have an important role in determining the quality of human behavior in carrying out tasks and social relations with other people in everyday life. In studying together and interacting with others, the ability to manage emotions is needed well, controlled emotional conditions will be able to bring harmonious relationships to encourage learning activities, but preferably when managing emotions that are not controlled or emotions in an unstable manner will lead to disharmonious relationships and lack of enthusiasm in learning Disharmonious relationships will have an effect on poor quality learning processes, and social problems between individuals who interact. In Islamic perspective, adherents are encouraged to be able to manage emotions well, controlled and mature emotional management can make it easier for adherents of Muslims to develop or increase their understanding of Islamic values ​​and to improve friendly relations among Muslims and among other religious communities. One form of emotion is anger. Many arguments in the Hadith and the Qur'an talk about holding back or controlling anger, in this case managing uncontrollable emotions. The purpose of this writing is to describe the importance of managing emotions in everyday life and matters relating to the Islamic view of managing emotions. The method in this writing is literature study, namely by explaining and analyzing several psychological theories and Islamic views on Emotion Regulation.